(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This article explores the integration processes within military education systems, emphasizing their critical role in modernizing curricula and addressing the dynamic needs of national and international security. The aim is to analyze integration models and strategies that combine civilian and military education, theoretical and practical training, and traditional and innovative teaching methodologies. Using a systematic and comparative approach, the study evaluates global practices and specific examples from Bulgaria and NATO member states to identify effective integration strategies.The research highlights the importance of fostering synergy between diverse educational components to enhance the preparation of military personnel for evolving defense challenges. Integration models, such as dual and modular training and institutional cooperation, are analyzed for their potential to combine military and civilian expertise. The integration of theoretical knowledge with practical training, including the use of simulations, field exercises, and joint international training, is shown to be critical for developing problem-solving skills and operational readiness. Furthermore, balancing traditional and innovative teaching methods is identified as a means to foster critical thinking and adaptability in learners.The study concludes that integration is a strategic imperative for modern military education. Key recommendations include strengthening collaboration between military academies and civilian institutions, continuously updating curricula to reflect technological advancements, increasing opportunities for practical training, promoting flexible learning models, and investing in resources such as equipment, facilities, and teacher development. These measures are essential for preparing military professionals to meet the complexities of contemporary defense and security environments effectively.